Decoration behaviour in a spider crab, Acanthonyx scutiformis (Dana, 1851) in relation to life stage, sex and algal species - De Carvalho, F. R.P.; Rodrigues, R. De O. [UNESP]; Barreto, R. E. [UNESP]; Costa, Tânia Marcia [UNESP] (Brill Academic Publishers, 2016)
In this study we evaluated the types of algae chosen for decorating by the spider crab Acanthonyx scutiformis (Dana, 1851) and determined whether decorating is more common in juvenile or adult crabs and in females or males (adult). In field observations we found that spider crabs in each age group or sex have an equal probability of being decorated. There were no differences in this behaviour between sexes in the laboratory. However, juvenile spider crabs engaged more in decoration behaviour than adult crabs in laboratory observations and decorated with the same algae that they used for decorating in nature. Thus, in conditions that represent an increased risk of predation, juvenile crabs have an increased need to attach algal fragments onto their carapaces, whereas the body size of adult spider crabs renders them less vulnerable to predators, thus reducing their need for decoration.